2022
DOI: 10.1590/fst.119121
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenic compounds removal and characteristics of non- and pregelatinized traditional detoxified wild yam (Dioscorea hispida) tuber flour

Abstract: The presence of cyanide compounds restricts the utilization of wild yam (Dioscorea hispida) tubers for food or food ingredients. Traditional detoxification, usually used in wild yam chips processing, has not been evaluated for its effectiveness in reducing cyanogenic compounds. Processing into flour will increase wild yam tubers utilization and pregelatinization usually improve flour functional properties. This study aimed to evaluate the effect of 4 traditional detoxification methods and pregelatinization on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Four traditional detoxification methods from four locations (Kandangan Sub-district, Kediri Regency; Paiton Sub-district, Probolinggo Regency; Wates Sub-district, Kediri Regency; Ngaglik Sub-district, Blitar Regency) were conducted at the laboratory for analysis of the pH at every step in wild yam tuber chips processing. The cyanogenic changes during wild yam chips processing were from our previous study [ 22 ]. The discussion to elucidate the scientific evidence behind every step of wild yam tuber detoxification based on the relevant literature.…”
Section: Methods Of Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Four traditional detoxification methods from four locations (Kandangan Sub-district, Kediri Regency; Paiton Sub-district, Probolinggo Regency; Wates Sub-district, Kediri Regency; Ngaglik Sub-district, Blitar Regency) were conducted at the laboratory for analysis of the pH at every step in wild yam tuber chips processing. The cyanogenic changes during wild yam chips processing were from our previous study [ 22 ]. The discussion to elucidate the scientific evidence behind every step of wild yam tuber detoxification based on the relevant literature.…”
Section: Methods Of Reviewmentioning
confidence: 99%
“…HCN content of wild yam tuber was 84.26 ppm [ 31 ], and total cyanide content of 379–739 ppm [ 32 ]. The previous study [ 22 ] showed that wild yam tuber contained HCN of 54.74 ± 0.17 ppm, acetone cyanohydrin of 3.91 ± 0.28 ppm, a cyanogenic glycoside of 24.55 ± 0.21 ppm, and total cyanides of 83.20 ± 0.11 ppm. FAO/WHO determined that the safe limit of cyanide ingestion is 10 ppm [ 33 ].…”
Section: Cyanogenic Compounds Removal In the Steps Of Wild Yam Tuber ...mentioning
confidence: 99%
See 3 more Smart Citations